(untitled) (diségno, 2021)
The need to ‘connect’ appears, today, stronger the more pervasively the tendency to ‘separate’ and build barriers manifests itself. And it is exactly those physical and/or virtual barriers, in a broad sense, which are the places where the conflict between peoples and cultures are manifested, the background of a narrative horizon that will be tentatively explored, renouncing first of all the consideration of architecture as a neutral protagonist of this story, but declaring, instead, right from the start, the impossibility of its ‘innocence’ (read more).